Description of a new species of simulium (Gomphostilbia) (Diptera: Simuliidae) from Cameron's Highlands, peninsular Malaysia, With Keys to 18 species of the simulium asakoae species-Group - Takaoka, H.; Sofian-Azirun, Mohd; Hashim, R. (2013)
Simulium (Gomphostilbia) izuae sp. nov. is described from female, male, pupal, and larval specimens collected from Cameron's Highlands, Peninsular Malaysia. This new species is placed in the asakoae species-group of the subgenus Gomphostilbia. The pupa of this new species is characterized by the gill with eight long filaments arranged as (3 + 3) + 2 filaments, of which the ventral pair of filaments is borne on a stalk that is always shorter than the common basal stalk. Taxonomic notes to distinguish this new species from five other Malaysian species and 12 other species of the asakoae species-group from other countries are given. Keys to identify all 18 species of the asakoae species-group are also provided for females, males, pupae, and mature larvae.